2017
DOI: 10.1111/maps.12857
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of central pit craters on Mars, Mercury, Ganymede, and the Saturnian satellites

Abstract: We report on the first results of a large‐scale comparison study of central pit craters throughout the solar system, focused on Mars, Mercury, Ganymede, Rhea, Dione, and Tethys. We have identified 10 more central pit craters on Rhea, Dione, and Tethys than have previously been reported. We see a general trend that the median ratio of the pit to crater diameter (Dp/Dc) decreases with increasing gravity and decreasing volatile content of the crust. Floor pits are more common on volatile‐rich bodies while summit … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 44 publications
(126 reference statements)
2
14
0
Order By: Relevance
“…When we examine the distribution of crater morphologies, there are definitely nonrandom distributions of different morphologies within a diameter bin. Our results corroborate nonrandom spatial distributions of hollows (Blewett et al, ; Thomas et al, ), pits attributable to explosive volcanism (Thomas et al, ), and central‐crater pits that other researchers have observed (Barlow et al, ; Xiao & Komatsu, ). We add to these our observations of crater central structures for craters with D ≈ 100 km (Figure ), particularly the distinction between craters with some form or ringed peak and those with a single central structure or multiple unorganized central structures.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…When we examine the distribution of crater morphologies, there are definitely nonrandom distributions of different morphologies within a diameter bin. Our results corroborate nonrandom spatial distributions of hollows (Blewett et al, ; Thomas et al, ), pits attributable to explosive volcanism (Thomas et al, ), and central‐crater pits that other researchers have observed (Barlow et al, ; Xiao & Komatsu, ). We add to these our observations of crater central structures for craters with D ≈ 100 km (Figure ), particularly the distinction between craters with some form or ringed peak and those with a single central structure or multiple unorganized central structures.…”
Section: Discussionsupporting
confidence: 89%
“…On Mars and some of the outer‐planet satellites (e.g., Barlow et al, ; Barlow & Bradley, ; Schenk, ; Xiao & Komatsu, ) a small circular central‐pit either in place of or atop a crater's central peak has been identified as a common crater landform that comprises a large percentage (>10%) of well‐preserved craters in certain diameter ranges. On Mercury a small number of craters have pits analogous to those atop a central peak (central‐structure summit pit, 21 craters) or on the crater floor in place of central peak (central‐structure floor pit, 1 crater).…”
Section: Methodsmentioning
confidence: 99%
“…Previous investigations have described and investigated the relationships of spatial distribution and target properties (including rock type) with different types of impact craters, including different types of central pit craters (e.g., Barlow, 2011;Barlow, 2017). Both summit and floor central pit craters span the midlatitudes and all longitudes of Mars, although there is a dearth of both CPCs and central peak craters on Tharsis and in Hellas and Argyre basins (see below, Figure 3).…”
Section: Mars Central Pit Craters: Location and Size Distributionsmentioning
confidence: 99%
“…the conclusion that a component of structural uplift is likely required for central pit formation (Bray et al, 2009;Barlow et al, 2017).…”
Section: 1029/2018je005738mentioning
confidence: 99%
See 1 more Smart Citation